UPAYA MENINGKATKAN AKTIVITAS DAN PRESTASI BELAJARMATEMATIKA DENGAN MODEL PEMBELAJARANKOOPERATIF TIPE THINK PAIR SHARE (TPS)DISERTAI BOLA PANTAI BAGI SISWAKELAS IV SDN KLAGARAN - Siti Nur Janah; Ag. Sri Purnami (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2015)
Â Abstract: The purposes of this research is to improve the activity and learning outcomes in mathematics of students 4th grade Klagaran Public Elementary School through cooperative learning type Think Pair Share with beach ball. The subjects of this research were 24 students of 4th grade Klagaran Public Elementary. The object of this research was studentâ€™s activity and mathematics learning outcomes. The result showed that after treatment with cooperative learning type Think Pair Share with beach ball at 4th grade Klagaran Public Elementary School, activity and mathematics learning outcomes of students has increased. This was indicated by an increasing in the result percentage average activity is70,83% at the first cycle, improves in the second cycle to 100%. Mathematics learning outcomes of students also increased. The average of students learning outcomes in pre-action was 61,54. In the first cycle, the average result improves to 65,00. In the second cycle, the average result improves to 65,59. In conclusion, cooperative learning type Think Pair Share with beach ball can improve activity and mathematics learning outcomes.